Shifting Emotional Expression in Lithuanian Love Songs - Buivytė, Giedrė (Tautosakos darbai, 2022)
The article focuses on social and cultural background of the shifts taking place in the stylistics and contents of Lithuanian love songs. Applying theoretical assumptions from the field of history of emotions, the author analyzes shifting expression of emotions in folksongs on the topic of love. The subject of the article embraces love songs that spread from the 19th to the first half of the 20th century and were shaped not only by the folklore tradition, but also by Lithuanian and foreign poetry of the time, and by popular romances. These compositions differ in terms of poetic quality, displaying both the traditional folksong elements and changing attitudes by the singers and people that are depicted in the songs, as well as a new vocabulary of emotional expression. Applying insights by Peter N. and Carol Z. Stearns (1985) regarding the society’s standards on the expression of emotions, and the concept of emotive, or emotional statement, introduced by W. Reddy (2001), the author regards the shifting expression of emotions in love songs as a reflection of emotionality spreading in written culture (primarily poetry) of the 19th century. Utterances of love-related emotions are essentially perceived as manifestations of the changing poetic vocabulary. The first chapter discusses social and cultural conditions of the changing folksongs, concentrating mostly on the notion of love and its significance in traditional Lithuanian peasant family, and the spread of literacy in the 19th century. The growth of written culture is considered a factor in introducing tropes and prototypes of emotional language that express the notion of romantic love into the sphere of folksong. The second chapter analyzes the relationship between love songs and individual poetry. Various collections of Lithuanian folksongs published in the 19th century, as well as their publications in the press testify to the process of interaction between written and oral culture gaining momentum at that time. This process was further stimulated by the increase of Lithuanian poetry composed by representatives of Lithuanian intelligentsia and literati with roots among the small noblemen and peasants; their compositions were significantly influenced by foreign poetry. Romantic lyrics also grew popular among the peasants. The third chapter explores the distinction between classical folksongs that encode communication of the young people in symbols and draw on the ritual code, and the new love songs that preserve traditional images but lose their symbolic meaning and ritual orientation. The author concludes that these new love songs employ a predominantly poetic vocabulary of emotional expression typical to written culture, their folkloric formulas mixing with new phrases yet unpolished by the tradition and straightforwardly naming certain emotions; a direct relation between “I” and “you” becomes more prominent too. She discusses samples of folksongs that directly name love and openly depict such related emotions as worry, sorrow, or anger, and loveʼs parallel with death.To sum up, it is stated that expressions of personal emotions increasingly become established in the new love songs. Although such expressions are frequently artistically rough and unpolished, they testify to the necessity of mastering new means of poetic expression, acutely felt by the newly literate people. Moreover, the songs also expand the semantic field of love, associating this feeling with intense emotions, overwhelming anxiety and longing, while the absence of love is conceptualized as a failing health and lost inner peace. Obviously, the stylized and frequently sentimental poetic vocabulary of emotional expression, characteristic to individual poetry affected by foreign literature and romances, presented new possibilities to discuss emotions in folksongs. These practices should be regarded mainly as “legitimization” of a new emotionally expressive rhetoric in the sphere of folkloric communication rather than a direct testimony to the experienced feelings.
Keywords: love songs; romance; emotional expression; love; written culture